Living Arrangements, Offspring Migration, and Health of Older Adults in Rural China: Revelation From Biomarkers and Propensity Score Analysis - Song, Qian (J Aging Health, 2018)
OBJECTIVE: We examine the combined effects of living arrangements and outmigration of adult children on rural older adults’ health profiles, measured by biomarker data from the China Health and Retirement Longitudinal Study 2011. METHOD: We employ biomarker data and propensity score analysis which allows us to effectively deal with selection issues that are commonly observed in the literature. RESULTS: We show complex health implications of living arrangements and offspring migration. Living in a traditional multigenerational household has limited health benefits to older adults. However, older parents of migrants who live in a multigenerational household have better fitness in blood pressure. Their advantage over parents of migrants in other living arrangements suggests added benefits of the presence of grandchildren. DISCUSSION: This study bridges the living arrangement and migration literature on health by showing that health effects of adult children’s migration on older adults are contingent upon their living arrangements.